TOURISM AND CONSERVATION MANAGEMENT OPTIONS FOR KARIMUNJAWA MARINE NATIONAL PARK (Case Study and Reviews) - Frida Purwanti (JOURNAL OF COASTAL DEVELOPMENT, 2001)
Tourism is a nature-based industry that will have impacts on the environment. In order to achieve successful and sustainable tourism, tourism development and conservation of natural resources have to go hand in hand. This will be only attained through an environmental strategic tourism planning approach. Karimunjawa islands as one of the largest marine protected areas in Indonesia, provide a wide range of opportunities for research and environmental education as well as for tourism and recreation. In 1995, the Central Java Government conducted a tourism development study, but the study failed to assess current tourist market. This study intent to analyse the existing tourist market and to offer management guidelines. The study was conducted using qualitative methods to analyse the existing tourism market and its’ development plan by reviewing and examining the primary and secondary sources. The study revealed that local residents are not fully involved in the development of the tourism plan. It is considered that, at least initially, tourism in the Karimunjawa Islands should be developed on a selective and small-scale base. It is recommended that a development manual, guidelines and policies be prepared in support of the tourism development plan. Public education program and involvement of the local community should be encouraged to support the tourism plan. The proposed management guidelines cover three issues : the environmental impact of tourism development; the appropriate institutional and legal framework to regulate and monitor tourism development, especially on the islands; and the extent of local community participation